Envelhecer num corpo jovem: exercício físico e dispositivo biopolítico de rejuvenescimento - Teixeira, Fábio Luís Santos (2017)
ABSTRACT The objective of this work was to analyze the strategies of knowledge, power and subjectivation that constitute the biopolitical device of rejuvenation and that give it form and make it work based on the problematizations made on physical exercise. Allied to this, we try to discuss how the subjects, in their personal experience of taking care of the body, acquire speeches, take practices and reinvent rules of conduct (government) that base corporal rejuvenation as a hermeneutic and transforming way of life. It is a qualitative research that was developed from the analysis of two printed media (the magazine Boa Forma and the magazine Women's Health), analysis of discourses of science through a systematic review carried out at PUBMED, analysis of the main scientific periodical of the area and interview with women practicing physical exercise and consumers of rejuvenation technologies. Different lines were identified that constitute the biopolitical device of rejuvenation. Lines of power, knowledge, resistance, fight, visibility, discourse, and ruptures revealed that bodily rejuvenation refers to the importance of retaking an earlier physical structure or returning to a previous subjective and biological experience. The discourses also indicate that rejuvenation means not a recovery of the chronological age, but of a biological state marked by the absence of the associated aesthetic, biological and social declines, as well as of fattening, appearance of wrinkles, cellulites, sagging, white hair. It was possible to find several evidences that support the idea of physical exercise as a rejuvenation technique. Dusting lines have been identified that refer to the production of rejuvenation as a technique of the self. In this sense, body rejuvenation is associated with behavioral vigilance, happiness and the ability to make healthy choices. Therefore, having a rejuvenated body requires being happy with the body or maintaining a "high spirits" that contributes to the acquisition of a rejuvenated way of being. This means breaking with the hegemony of biological control that characterizes the stainless bodies made possible by the technological domination of life.